Implementasi Manajemen Dakwah dalam Penguatan Karakter Peduli Kebersihan Lingkungan pada Siswa SD Islam Kamaliah Pematang Johar - Suci Nabila; Muhammad Fachran Haikal (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This research intends to examine the implementation of da'wah management in shaping students' character and awareness of environmental cleanliness at Kamaliah Islamic Elementary School, Pematang Johar. The observed phenomenon arises from students' variable actions regarding school cleanliness, even with an effective program in place. This research adopts a qualitative approach, employing an intrinsic case study to investigate the processes, importance, and interactions related to the implementation of da'wah management in Islamic primary schools. Data was gathered via thorough interviews with the principal, educators in Islamic Religious Education, classroom teachers, and students, along with observations of documents and participant interactions. The analysis of data was performed interactively, encompassing data reduction, data presentation, and the formulation and verification of conclusions. The results of the research suggest that the implementation of da'wah management is carried out through four main functions: planning, organizing, implementing, and monitoring. Planning includes the integration of cleanliness values ​​as part of faith into school programs. Classroom-based organizing involves collaboration between teachers and students. Implementation prioritizes habituation, role modeling, and strengthening religious values, while supervision is carried out through daily monitoring, monthly evaluations, and a reward system. These findings indicate that structured da'wah management helps internalize environmental values ​​more systematically. This research contributes to the strengthening of the theory of integrated Islamic-based character education and management, and provides practical recommendations for schools in developing sustainable and contextual character development models.